Keycloak - identity and access management for modern applications harness the power of keycloak, openid connect, and oauth 2.0 to secure applications - Thorgersen, Stian; Silva, Pedro Igor (Packt Publishing, 2023)
The second edition of Keycloak - Identity and Access Management for Modern Applications is an updated, comprehensive introduction to Keycloak and its updates. In this new edition, you will learn how to use the latest distribution of Keycloak. The recent versions of Keycloak are now based on Quarkus, which brings a new and improved user experience and a new admin console with a higher focus on usability. You will see how to leverage Spring Security, instead of the Keycloak Spring adapter while using Keycloak 22. As you progress, you'll understand the new Keycloak distribution and explore best practices in using OAuth. Finally, you'll cover general best practices and other information on how to protect your applications. By the end of this new edition, you'll have learned how to install and manage the latest version of Keycloak to secure new and existing applications using the latest features.
Keywords: Software protection-Computer programs; Web applications